KALIMAT INTEROGATIF PADA TUTURAN SANTRI PUTRI PONDOK PESANTREN RAUDLATUL ULUM 1 GANJARAN GONDANGLEGI MALANG - Hamidah; Hosniyeh (Jurnal Studi Pesantren, 2020)
Interrogative sentences are included in a variety of sentences or called sentence types, the researcher examines more deeply the interrogative sentences spoken by Santri Pondok Pesantren Raudlatul Ulum 1 Putri Ganjaran Gondanglegi Malang. The focus of this research is on the analysis of: 1) how the total interrogative sentences in the speech of female students of the Raudlatul Ulum Islamic Boarding School 1 Putru Ganjaran Gondanglegi Malang, 2) how the partial interrogative sentences on the speech of female students of the Raudlatul Ulum Islamic Boarding School 1 Ganjaran Gondanglegi Malang. This study aims to determine how total interrogative sentences and partial interrogative sentences have been spoken by female students at the Raudlatul Ulum 1 Ganjaran Gondanglegi Islamic Boarding School Malang. This study uses a descriptive research method with a qualitative approach because this research is descriptive, using listening, recording, and note-taking techniques. The conclusion of this study is that the interrogative sentences spoken by the administrator to the students of the Raudlatul Ulum Islamic Boarding School 1 Putri Ganjaran Gondanglegi Malang do not match the intended intonation, and sometimes do not use question words and sometimes use question words at the beginning of sentences in telling partial sentences. Keywords: Speech, Interrogative Sentence